2021
DOI: 10.3390/ph14090915
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Properties of Antidepressants and Antipsychotics—Possibilities and Implications

Abstract: The spreading of antibiotic resistance is responsible annually for over 700,000 deaths worldwide, and the prevision is that this number will increase exponentially. The identification of new antimicrobial treatments is a challenge that requires scientists all over the world to collaborate. Developing new drugs is an extremely long and costly process, but it could be paralleled by drug repositioning. The latter aims at identifying new clinical targets of an “old” drug that has already been tested, approved, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 118 publications
0
13
0
Order By: Relevance
“…Numerous evidence supports the theory that serotonin reuptake inhibitors, the main antidepressant class of drugs, are efficient antimicrobial drugs, attributable to their activity in the suppression of efflux pumps [ 41 , 42 , 43 ] ( Table 2 ). In 2015, Ayaz et al [ 44 ] explored the potential activity of sertraline against ATCC strains, clinical isolates of S. aureus , E. coli, and P. aeruginosa , alone and in combination with seven antibiotics.…”
Section: Antidepressants and Antipsychoticsmentioning
confidence: 90%
See 1 more Smart Citation
“…Numerous evidence supports the theory that serotonin reuptake inhibitors, the main antidepressant class of drugs, are efficient antimicrobial drugs, attributable to their activity in the suppression of efflux pumps [ 41 , 42 , 43 ] ( Table 2 ). In 2015, Ayaz et al [ 44 ] explored the potential activity of sertraline against ATCC strains, clinical isolates of S. aureus , E. coli, and P. aeruginosa , alone and in combination with seven antibiotics.…”
Section: Antidepressants and Antipsychoticsmentioning
confidence: 90%
“…Phenothiazines are compounds mainly used to treat psychotic disorders, and their primary antipsychotic action seems to be based on the suppression of dopamine by blocking the dopaminergic receptors. Some studies demonstrated that many derivatives, such as chlorpromazine, thioridazine, and trifluoperazine, also possessed antimicrobial activities [ 15 , 25 , 41 ]. In terms of the mechanism of action, phenothiazines are able to reduce pathogen adhesion in endothelial cells.…”
Section: Antidepressants and Antipsychoticsmentioning
confidence: 99%
“…Despite the heterogeneity in psychopharmaceuticals' chemical composition, most have antibacterial activity (Caldara and Marmiroli, 2021; Table 1) For example, it has been studied that taking antidepressants, especially fluoxetine, amitriptyline, venlafaxine, paroxetine, mirtazapine and trazodone, affecting the composition of the intestinal microbiota (Kalaycı et al, 2014), elevates the risk towards Clostridioides difficile infection (Rogers et al, 2013). The relationship between the qualitative and quantitative composition of The impact of certain factors on one's behavior.…”
Section: Psychiatric Treatmentmentioning
confidence: 99%
“…The antimicrobial effects of different non-antibiotic drugs have been reported, including statins and non-steroidal anti-inflammatory drugs (NSAIDs), as well as cytostatics and psychotropics [ 39 , 40 ]. Some antidepressant drugs demonstrated antimicrobial effects, being the highest activity evidenced in the third-generation antidepressants known as selective serotonin reuptake inhibitors (SSRIs), such as fluoxetine, paroxetine, and sertraline [ 41 ]. Among them, sertraline, due to its antimicrobial potential, enhanced the activity of different antibiotics, counteracted the multidrug resistance of pathogens, and made them susceptible to previously resistant drugs [ 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%